2013
DOI: 10.1002/ebch.1916
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies for the treatment of post‐traumatic stress disorder in children and adolescents (Review)

Abstract: There is evidence for the effectiveness of psychological therapies, particularly CBT, for treating PTSD in children and adolescents for up to a month following treatment. At this stage, there is no clear evidence for the effectiveness of one psychological therapy compared to others. There is also not enough evidence to conclude that children and adolescents with particular types of trauma are more or less likely to respond to psychological therapies than others. The findings of this review are limited by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 118 publications
5
56
1
2
Order By: Relevance
“…Significant pre-post effect sizes were achieved using established interventions like CBT, IPT, and EMDR. This, again, is in line with the meta-analysis of Gillies et al (2013), who showed that exposure-based interventions in children and adolescents from the general population had larger effects on depression symptoms than other psychological approaches. CBT treatments resulted in an overall small to medium pre-post effect size for depressive symptoms (SMC = 0.30) in this group, which is lower than psychotherapy effects in general population minors with mixed traumata (Gillies et al, 2013: SMD = 0.80 compared to any control condition; Gutermann et al, 2016: SMC = 0.62; Morina et al, 2016: SMD = 0.30 compared to waitlist controls).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Significant pre-post effect sizes were achieved using established interventions like CBT, IPT, and EMDR. This, again, is in line with the meta-analysis of Gillies et al (2013), who showed that exposure-based interventions in children and adolescents from the general population had larger effects on depression symptoms than other psychological approaches. CBT treatments resulted in an overall small to medium pre-post effect size for depressive symptoms (SMC = 0.30) in this group, which is lower than psychotherapy effects in general population minors with mixed traumata (Gillies et al, 2013: SMD = 0.80 compared to any control condition; Gutermann et al, 2016: SMC = 0.62; Morina et al, 2016: SMD = 0.30 compared to waitlist controls).…”
Section: Discussionsupporting
confidence: 88%
“…The analysis of pre-post effects confirmed the positive effects for CBT, but there were some other treatments with positive pre-post effects that might be promising candidates for future investigation: EMDR, meditation-relaxation, an educational programme in schools as developed by the UNESCO, a stepped systemic treatment designed to the needs of young refugee youth, and writing for recovery. The positive CBT and EMDR effects are in line with the recent literature on youth from the general population (Gillies, Taylor, Gray, O’Brien, & D’Abrew, 2013; Gutermann et al, 2016). The mean pre-post effect size in our study cannot be meaningfully interpreted due to the high heterogeneity, which has also been reported in a number of other meta-analyses (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…According to Gillies, Taylor, Gray, O'Brien and D'Abrew (2013) who have conducted 14 meta-analysis studies, state that non-pharmacologic treatment of PTSD in teenagers can be accomplished by conducting CBT therapy that proves to be more significant than other types of psychotherapy. According to Stuart (2016), Cognitive Behavior Therapy (CBT) is one action that can be performed to succeed PTSD problems.…”
Section: Introductionmentioning
confidence: 99%